Discourse and power in the Gospel according to Mark: Strategies of exclusion - Smit, Johannes A. (Koers, 1993)
In this article it is argued that the materiality of religious discourse necessitates a description of its strategies of power and control. Since Christian religious discourse reactivates the discourses of canonical writings, the description of the materiality of the discursive practices of the canonical writings themselves is imperative. Focusing on the strategics of exclusion, Foucault’s archaeological model of the description of discourse is used as a framework for delineating some strategies of the Markan discourse. The analysis of the archive ... involves a privileged region: at once close to us, and different from our p resent existence, it is the border of time that surrounds our presence, which overhangs it, and which indicates it in its otherness; it is that which, outside ourselves, delimits us (Foucault, 1972:130).